CLIMATE CHANGE EFFECTS ON THE DISTRIBUTION, PREVALENCE AND TRANSMISSION DYNAMICS OF INFECTIOUS DISEASES IN RURAL SINDH - Zahid Hussain Mirani; Junaid Ali Sohu; Muhammad Idrees Rahoojo; Mr Muhammad Shoaib Bozdar; Rahmatullah Soomro (International Journal of Contemporary Issues in Social Sciences, 2024)
The current study has been undertaken to take insightful data through the medical experts and affected population of climate change effects in the context of infectious disease distribution, prevalence and transmission dynamics in the rural Sindh province of Pakistan. Therefore; the warmer regions of Rural Sindh were selected for the data collection of the study. The Jacobabad, Shikarpur and Larkana districts were regions for data collection. In-depth interviews were organized to collect the data from the targeted population. 8 in-depth interviews were taken from the medical experts in the respective districts of targeted population, however; 10 in-depth interviews were conducted with the individuals within the affected population of these three districts. The data were analyzed using QDA minor latest version which is convenient for the qualitative data analysis. The findings of the study reveals that the climate change has sever effects on the human health. Due to the warmer weather, rise in temperature is conducive for outbreak of the infectious disease which is inevitable causing life as well as economic loss. According to the medical experts, future will be worst ever in the context of climate change effects and impacts on the human societies in terms of health hazardous if the proper health systems are not applied in the region. The series of floods in this region of Sindh is an eye witness of rapid spread of infectious diseases such as Malaria which recorded high rate of morbidity and mortality in the rural Sindh. Poor infrastructure, improper health facility centers required medical appliances, people’s health awareness are the major reasons to prevent the population from the hazardous in future. This study can be a key player in understanding the climate change affects in the rural areas of Sindh from the people perspectives who are health care professionals and affected local population those regions.